2015
DOI: 10.1590/s1517-707620150004.0089
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação numérica da influência da geometria do ferramental na geração de tensões residuais durante o processo de trefilação de barras de aço

Abstract: RESUMOTrefilação é um processo de fabricação que consiste na redução da área de seção transversal de um material, quando este atravessa uma matriz cônica, chamada fieira. Devido às características inerentes ao processo, as deformações são heterogêneas ao longo da seção do material, originando tensões residuais, que podem contribuir com o aparecimento de distorções, propagação de trincas e consequentemente acarretar em redução da vida útil do produto final. Neste trabalho, foi analisada a influência da geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…The Variations in radial stress affect the mechanical properties, and subsequently, the quality of the drawn product, which might lead to disqualification. Such defects include shape distortion, crack propagation, inferior surface finish quality, and reduced dimensional accuracy [13][14][15][16][17]. For instance, it has been demonstrated in [18,19] that the radial stress due to specific die bearing contour geometry has a significant impact on the degree of residual stress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Variations in radial stress affect the mechanical properties, and subsequently, the quality of the drawn product, which might lead to disqualification. Such defects include shape distortion, crack propagation, inferior surface finish quality, and reduced dimensional accuracy [13][14][15][16][17]. For instance, it has been demonstrated in [18,19] that the radial stress due to specific die bearing contour geometry has a significant impact on the degree of residual stress.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies by Nakagiri [8], Coser [17], and Godfrey [23] focused on the effects of the wire/die contact length to diameter ratio (L/Di). Here the length of L is defined as the sum of the frustum slant length at 2β die angle and the length of the bearing zone Hc indicated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Obteve-se um valor médio por ponto medido e seu respectivo desvio padrão. Para objetos trefilados, a direção das tensões residuais de maior importância são as axiais [3,10], portanto, somente tensões axiais serão apresentadas. Os resultados obtidos em termos de tensões residuais foram agrupados segundo a seguinte classificação:…”
Section: Figuraunclassified
“…Isto pode ser atingido através da filosofia da "engenharia de distorção" [1] que visa entender o processo de fabricação como um todo, identificando possíveis portadores de potencial de distorção, atuando sobre eles e, consequentemente, reduzindo distorções durante todas as etapas do processo bem como no produto final [2,3]. Existem diversos potenciais de distorção identificados [4], mas, dentre eles, os mais estudados devido aos seus efeitos gerais no material são geometria, histórico mecânico, composição química, microestrutura e tensões residuais.…”
Section: Introductionunclassified
“…Vega, et al [26] studied the influence of the process parameters on the copper wire drawing and noticed that an increase in effective strain makes the deformation more inhomogeneous over the cross-section, especially near the die wire interface, thus leading to severe wire damage. Coser, et al [245] investigated the influence of the residual stress distribution in steel rods by changing the bearing geometry and length through numerical analysis and concluded that differing the bearing length (BL) in the ratio of 0.4D to 0.6D (where D is the diameter of the wire drawn) produced less residual stress on the wire surface. The research was analogous to the work of Overstam [246] who altered between two bearing geometry namely circular and tapered and concluded that tapered profile bearing has a better effect in reducing the inhomogeneous deformation in the wire.…”
Section: Introductionmentioning
confidence: 99%